Astrocytes as a Source for Extracellular Matrix Molecules and Cytokines - Wiese, Stefan; Karus, Michael; Faissner, Andreas (Frontiers in Pharmacology, 2012)
Research of the past 25 years has shown that astrocytes do more than participating and building up the blood brain barrier and detoxify the active synapse by reuptake of neurotransmitters and ions. Indeed, astrocytes express neurotransmitter receptors and, as a consequence, respond to stimuli. Deeper knowledge of the differentiation processes during development of the central nervous system (CNS) might help explaining and even help treating neurological diseases like Alzheimer’s disease, Amyotrophic lateral sclerosis (ALS) and psychiatric disorders in which astrocytes have been shown to play a role. Astrocytes and oligodendrocytes develop from a multipotent stem cell that prior to this has produced primarily neuronal precursor cells. This switch towards the more astroglial differentiation is regulated by a change in receptor composition on the cell surface and responsiveness of the respective trophic factors Fibroblast growth factor (FGF) and Epidermal growth factor (EGF). The glial precursor cell is driven into the astroglial direction by signaling molecules like Ciliary neurotrophic factor (CNTF), Bone Morphogenetic Proteins (BMPs), and EGF. However, the early astrocytes influence their environment not only by releasing and responding to diverse soluble factors but also express a wide range of extracellular matrix (ECM) molecules, in particular proteoglycans of the lectican family and tenascins. Lately these ECM molecules have been shown to participate in glial development. In this regard, especially the matrix protein Tenascin C (Tnc) proved to be an important regulator of astrocyte precursor cell proliferation and migration during spinal cord development. On the other hand, ECM molecules expressed by reactive astrocytes are also known to act mostly in an inhibitory fashion under pathophysiological conditions. In this regard, we further summarize recent data concerning the role of chondroitin sulfate proteoglycans and Tnc under pathological conditions.